Sustainable Amazonian Landcapes, Colombia socioeconomic survey - Quintero, Marcela; Vanegas, Martha; Pérez Marulanda, Lisset; Camilo, Karen; Cruz García, Gisella S.; Sachet, Erwan; Sosa, Chrystian; Castañeda Álvarez, Nora P.; Suarez Salazar, Juan C.; Angel, Katherine; Rico, Adrian; Solarte, Antonio; et al. (International Center for Tropical Agriculture, 2019)
The household survey was done in the four municipalities that are part of two landscape units from 30 March 2016 to 3 October 2016. A total of 341 households were surveyed, of which 176 (51, 6%) were from UP4 (hill) and 165 (48, 4%) from UP6 (mountainous). All the households that participated in the survey did it freely and under prior informed consent. Sampling was stratify across the two landscape units in order to take into account the different land use that farmers give to the land according to the biophysics conditions of its land. The data was collected through Android Devices using the software CsPro, and the data analysis was done through the statistical software package Stata (Reporte Interno: Linea Base Encuesta Socioeconomica Proyecto SAL, 2018). (2016)